Assessment of Quality Indexes in Colonoscopy in the Coloproctology Service of a Tertiary Private Hospital in Southern Brazil - Pinto,Rafael Castilho (2021)
Abstract Background Colorectal cancer (CRC) is the third most common cancer among men, and the second among women worldwide. In Brazil, the incidence andmortality of CRC continues to increase. In colonoscopies, adenoma detection rates (ADRs) higher than 25% are associated linearly with better outcomes and lower rates of interval cancer. Objective To assess the colonoscopy quality indexes. Methods This is a cross-sectional retrospective study in which anatomopathological data and data regarding the colonoscopies were collected from the patient records of Hospital Moinhos de Vento, in Southern Brazil. The exams were performed by doctors from the Colorectal Service from June to August 2015. Results A total of 430 exams were included. Most patients were women (60.9% [262]), with a mean age of 56.96 years. The cecal intubation rate was of 96.7% (416). The quality of the bowel preparation was excellent or good in 92.95% (396) of the cases. The average time of removal of the colonoscope in normal exams was of 6.15 minutes. Polyps were detected in 201 patients (46.7%), and adenomas, in 125 patients (29.1%); 12 patients (2.8%) had advanced adenomas, and 6 (2.3%) had malignant neoplasms. The proximal serrated lesion detection rate (PSLDR) was of 6.7% (29). The prevalence ratio (PR) of adenomas among men was 1.78 times greater than in women (95% confidence interval [95%CI]: 1.16-2.75). The PR of adenomas among people aged 50 years or older was 2.41 times that of those under 50 years of age (95%CI: 1.43-4.06). Conclusion The data obtained are in line with international quality criteria in colonoscopy. More studies are needed to assess the ADR in the Brazilian population.